Optimal. Leaf size=31 \[ 3+\frac {e^{-13+\frac {-1+x}{4 x}+x^2} (4-x)}{x}+x^2 \]
________________________________________________________________________________________
Rubi [F] time = 0.43, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {8 x^4+e^{\frac {-1-51 x+4 x^3}{4 x}} \left (4-17 x+32 x^3-8 x^4\right )}{4 x^3} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{4} \int \frac {8 x^4+e^{\frac {-1-51 x+4 x^3}{4 x}} \left (4-17 x+32 x^3-8 x^4\right )}{x^3} \, dx\\ &=\frac {1}{4} \int \left (8 x-\frac {e^{-\frac {51}{4}-\frac {1}{4 x}+x^2} \left (-4+17 x-32 x^3+8 x^4\right )}{x^3}\right ) \, dx\\ &=x^2-\frac {1}{4} \int \frac {e^{-\frac {51}{4}-\frac {1}{4 x}+x^2} \left (-4+17 x-32 x^3+8 x^4\right )}{x^3} \, dx\\ &=x^2-\frac {1}{4} \int \left (-32 e^{-\frac {51}{4}-\frac {1}{4 x}+x^2}-\frac {4 e^{-\frac {51}{4}-\frac {1}{4 x}+x^2}}{x^3}+\frac {17 e^{-\frac {51}{4}-\frac {1}{4 x}+x^2}}{x^2}+8 e^{-\frac {51}{4}-\frac {1}{4 x}+x^2} x\right ) \, dx\\ &=x^2-2 \int e^{-\frac {51}{4}-\frac {1}{4 x}+x^2} x \, dx-\frac {17}{4} \int \frac {e^{-\frac {51}{4}-\frac {1}{4 x}+x^2}}{x^2} \, dx+8 \int e^{-\frac {51}{4}-\frac {1}{4 x}+x^2} \, dx+\int \frac {e^{-\frac {51}{4}-\frac {1}{4 x}+x^2}}{x^3} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.15, size = 39, normalized size = 1.26 \begin {gather*} -\frac {1}{4} e^{-\frac {1}{4 x}+x^2} \left (\frac {4}{e^{51/4}}-\frac {16}{e^{51/4} x}\right )+x^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.57, size = 29, normalized size = 0.94 \begin {gather*} \frac {x^{3} - {\left (x - 4\right )} e^{\left (\frac {4 \, x^{3} - 51 \, x - 1}{4 \, x}\right )}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.27, size = 45, normalized size = 1.45 \begin {gather*} \frac {x^{3} - x e^{\left (\frac {4 \, x^{3} - 51 \, x - 1}{4 \, x}\right )} + 4 \, e^{\left (\frac {4 \, x^{3} - 51 \, x - 1}{4 \, x}\right )}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.06, size = 29, normalized size = 0.94
method | result | size |
risch | \(x^{2}-\frac {\left (x -4\right ) {\mathrm e}^{\frac {4 x^{3}-51 x -1}{4 x}}}{x}\) | \(29\) |
norman | \(\frac {x^{4}+4 \,{\mathrm e}^{\frac {4 x^{3}-51 x -1}{4 x}} x -{\mathrm e}^{\frac {4 x^{3}-51 x -1}{4 x}} x^{2}}{x^{2}}\) | \(49\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.49, size = 29, normalized size = 0.94 \begin {gather*} x^{2} - \frac {{\left (x e^{\frac {1}{4}} - 4 \, e^{\frac {1}{4}}\right )} e^{\left (x^{2} - \frac {1}{4 \, x} - 13\right )}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 1.91, size = 33, normalized size = 1.06 \begin {gather*} \frac {4\,{\mathrm {e}}^{x^2-\frac {1}{4\,x}-\frac {51}{4}}}{x}-{\mathrm {e}}^{x^2-\frac {1}{4\,x}-\frac {51}{4}}+x^2 \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.12, size = 22, normalized size = 0.71 \begin {gather*} x^{2} + \frac {\left (4 - x\right ) e^{\frac {x^{3} - \frac {51 x}{4} - \frac {1}{4}}{x}}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________